PEMBERDAYAAN LANSIA MELALUI LATIHAN JALAN TENDEM DALAM RANGKA MENGURANGI RESIKO JATUH - Febri Arifiati, Retna; Prasaja, Prasaja; Kurniawan, Hendri (Jurnal Indonesia Mengabdi, 2023)
Health is a basic and important element. Poor health conditions result in people being unable to regulate their own lifestyle and development in their area. As an emerging physiological syndrome in elderly health, frailty is a predictive factor of negative health outcomes, such as increased risk of death, decreased activities of daily living. This Community Service Activity aims to create a community that has knowledge and abilities, especially the elderly, especially in the health sector. The government's basic concept in developing elderly health program services aims to enable elderly people to live healthy lives by optimizing physical, mental, cognitive and spiritual functions through various promotive, preventive, curative and rehabilitative efforts including elderly empowerment programs in the community (Ministry of Health, 2020). One of the elderly empowerment programs is to reduce the risk of falls through tendem walking exercises. Tendemic walking exercises are exercises, attitudes or body positions to control balance, muscle coordination and body movements in order to reduce the risk of falls which often occur in the elderly. The aim of this community service activity is to empower the elderly by providing walking balance training in order to reduce the risk of falls in Tohudan Wetan Village, Colomadu, Karanganyar, Central Java. The target for counseling is 30 participants. Method. The method used is quantitative descriptive. The instrument used was a material understanding questionnaire containing 12 closed questions. This counseling aims to optimize the understanding of the elderly in order to minimize the risk of falls through walking balance exercises. The evaluation method used is a questionnaire to assess understanding of the pre- and post-activity counseling material. Results. Elderly empowerment activities are carried out through lecture methods, discussions and distribution of material leaflets. Material regarding the understanding and knowledge of elderly people about the risk of falling, risk factors for falling, understanding the tendem walk, implementation of the tendem walk exercise carried out every day in the morning and evening for one week with a duration of 10-15 minutes, the benefits of the tendem walk, evidence base of the tendem walk. The results of discussions carried out with the elderly showed that there was a change in knowledge about the importance of doing balance exercises in the form of tendem walking to reduce the risk of falls which often occur in the elderly. Conclusion. Based on the pretest and posttest results, a value of 0.000 (p<0.005) was obtained, meaning (1) tandem walking exercises provide increased information for the elderly in an effort to prevent the risk of falls (2) tandem walking exercises can improve balance in the elderly, (3) elderly people agree to do the exercises This tendem balance walk is carried out routinely, both individually and in groups, (3) this activity requires follow-up and cooperation between village officials, elderly organization administrators, health cadres and the elderly so that this training program can be continued.